6.7 Problems 601 to 700

Table 6.13: Main lookup table sequentially arranged

#

ODE

Mathematica

Maple

601

\[ {}[x^{\prime }\left (t \right ) = -3 y \left (t \right ), y^{\prime }\left (t \right ) = 3 x \left (t \right )] \]

602

\[ {}[x^{\prime }\left (t \right ) = 3 x \left (t \right )-2 y \left (t \right ), y^{\prime }\left (t \right ) = 2 x \left (t \right )+y \left (t \right )] \]

603

\[ {}[x^{\prime }\left (t \right ) = 2 x \left (t \right )+4 y \left (t \right )+3 \,{\mathrm e}^{t}, y^{\prime }\left (t \right ) = 5 x \left (t \right )-y \left (t \right )-t^{2}] \]

604

\[ {}[x^{\prime }\left (t \right ) = t x \left (t \right )-{\mathrm e}^{t} y \left (t \right )+\cos \left (t \right ), y^{\prime }\left (t \right ) = {\mathrm e}^{-t} x \left (t \right )+t^{2} y \left (t \right )-\sin \left (t \right )] \]

605

\[ {}[x^{\prime }\left (t \right ) = y \left (t \right )+z \left (t \right ), y^{\prime }\left (t \right ) = x \left (t \right )+z \left (t \right ), z^{\prime }\left (t \right ) = x \left (t \right )+y \left (t \right )] \]

606

\[ {}[x^{\prime }\left (t \right ) = 2 x \left (t \right )-3 y \left (t \right ), y^{\prime }\left (t \right ) = x \left (t \right )+y \left (t \right )+2 z \left (t \right ), z^{\prime }\left (t \right ) = 5 y \left (t \right )-7 z \left (t \right )] \]

607

\[ {}[x^{\prime }\left (t \right ) = 3 x \left (t \right )-4 y \left (t \right )+z \left (t \right )+t, y^{\prime }\left (t \right ) = x \left (t \right )-3 z \left (t \right )+t^{2}, z^{\prime }\left (t \right ) = 6 y \left (t \right )-7 z \left (t \right )+t^{3}] \]

608

\[ {}[x^{\prime }\left (t \right ) = t x \left (t \right )-y \left (t \right )+{\mathrm e}^{t} z \left (t \right ), y^{\prime }\left (t \right ) = 2 x \left (t \right )+t^{2} y \left (t \right )-z \left (t \right ), z^{\prime }\left (t \right ) = {\mathrm e}^{-t} x \left (t \right )+3 t y \left (t \right )+t^{3} z \left (t \right )] \]

609

\[ {}[x_{1}^{\prime }\left (t \right ) = x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 2 x_{3} \left (t \right ), x_{3}^{\prime }\left (t \right ) = 3 x_{4} \left (t \right ), x_{4}^{\prime }\left (t \right ) = 4 x_{1} \left (t \right )] \]

610

\[ {}[x_{1}^{\prime }\left (t \right ) = x_{2} \left (t \right )+x_{3} \left (t \right )+1, x_{2}^{\prime }\left (t \right ) = x_{3} \left (t \right )+x_{4} \left (t \right )+t, x_{3}^{\prime }\left (t \right ) = x_{1} \left (t \right )+x_{4} \left (t \right )+t^{2}, x_{4}^{\prime }\left (t \right ) = x_{1} \left (t \right )+x_{2} \left (t \right )+t^{3}] \]

611

\[ {}[x_{1}^{\prime }\left (t \right ) = 4 x_{1} \left (t \right )+2 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = -3 x_{1} \left (t \right )-x_{2} \left (t \right )] \]

612

\[ {}[x_{1}^{\prime }\left (t \right ) = -3 x_{1} \left (t \right )+2 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = -3 x_{1} \left (t \right )+4 x_{2} \left (t \right )] \]

613

\[ {}[x_{1}^{\prime }\left (t \right ) = 3 x_{1} \left (t \right )-x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 5 x_{1} \left (t \right )-3 x_{2} \left (t \right )] \]

614

\[ {}[x_{1}^{\prime }\left (t \right ) = 4 x_{1} \left (t \right )+x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = -2 x_{1} \left (t \right )+x_{2} \left (t \right )] \]

615

\[ {}[x_{1}^{\prime }\left (t \right ) = 4 x_{1} \left (t \right )-3 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 6 x_{1} \left (t \right )-7 x_{2} \left (t \right )] \]

616

\[ {}[x_{1}^{\prime }\left (t \right ) = 3 x_{1} \left (t \right )-2 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = -x_{1} \left (t \right )+3 x_{2} \left (t \right )-2 x_{3} \left (t \right ), x_{3}^{\prime }\left (t \right ) = -x_{2} \left (t \right )+3 x_{3} \left (t \right )] \]

617

\[ {}[x_{1}^{\prime }\left (t \right ) = x_{2} \left (t \right )+x_{3} \left (t \right ), x_{2}^{\prime }\left (t \right ) = x_{1} \left (t \right )+x_{3} \left (t \right ), x_{3}^{\prime }\left (t \right ) = x_{1} \left (t \right )+x_{2} \left (t \right )] \]

618

\[ {}[x_{1}^{\prime }\left (t \right ) = x_{1} \left (t \right )+2 x_{2} \left (t \right )+x_{3} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 6 x_{1} \left (t \right )-x_{2} \left (t \right ), x_{3}^{\prime }\left (t \right ) = -x_{1} \left (t \right )-2 x_{2} \left (t \right )-x_{3} \left (t \right )] \]

619

\[ {}[x_{1}^{\prime }\left (t \right ) = -8 x_{1} \left (t \right )-11 x_{2} \left (t \right )-2 x_{3} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 6 x_{1} \left (t \right )+9 x_{2} \left (t \right )+2 x_{3} \left (t \right ), x_{3}^{\prime }\left (t \right ) = -6 x_{1} \left (t \right )-6 x_{2} \left (t \right )+x_{3} \left (t \right )] \]

620

\[ {}[x_{1}^{\prime }\left (t \right ) = x_{1} \left (t \right )-4 x_{2} \left (t \right )-2 x_{4} \left (t \right ), x_{2}^{\prime }\left (t \right ) = x_{2} \left (t \right ), x_{3}^{\prime }\left (t \right ) = 6 x_{1} \left (t \right )-12 x_{2} \left (t \right )-x_{3} \left (t \right )-6 x_{4} \left (t \right ), x_{4}^{\prime }\left (t \right ) = -4 x_{2} \left (t \right )-x_{4} \left (t \right )] \]

621

\[ {}[x_{1}^{\prime }\left (t \right ) = x_{1} \left (t \right )+2 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 2 x_{1} \left (t \right )+x_{2} \left (t \right )] \]

622

\[ {}[x_{1}^{\prime }\left (t \right ) = 2 x_{1} \left (t \right )+3 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 2 x_{1} \left (t \right )+x_{2} \left (t \right )] \]

623

\[ {}[x_{1}^{\prime }\left (t \right ) = 3 x_{1} \left (t \right )+4 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 3 x_{1} \left (t \right )+2 x_{2} \left (t \right )] \]

624

\[ {}[x_{1}^{\prime }\left (t \right ) = 4 x_{1} \left (t \right )+x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 6 x_{1} \left (t \right )-x_{2} \left (t \right )] \]

625

\[ {}[x_{1}^{\prime }\left (t \right ) = 6 x_{1} \left (t \right )-7 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = x_{1} \left (t \right )-2 x_{2} \left (t \right )] \]

626

\[ {}[x_{1}^{\prime }\left (t \right ) = 9 x_{1} \left (t \right )+5 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = -6 x_{1} \left (t \right )-2 x_{2} \left (t \right )] \]

627

\[ {}[x_{1}^{\prime }\left (t \right ) = -3 x_{1} \left (t \right )+4 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 6 x_{1} \left (t \right )-5 x_{2} \left (t \right )] \]

628

\[ {}[x_{1}^{\prime }\left (t \right ) = x_{1} \left (t \right )-5 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = x_{1} \left (t \right )-x_{2} \left (t \right )] \]

629

\[ {}[x_{1}^{\prime }\left (t \right ) = 2 x_{1} \left (t \right )-5 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 4 x_{1} \left (t \right )-2 x_{2} \left (t \right )] \]

630

\[ {}[x_{1}^{\prime }\left (t \right ) = -3 x_{1} \left (t \right )-2 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 9 x_{1} \left (t \right )+3 x_{2} \left (t \right )] \]

631

\[ {}[x_{1}^{\prime }\left (t \right ) = x_{1} \left (t \right )-2 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 2 x_{1} \left (t \right )+x_{2} \left (t \right )] \]

632

\[ {}[x_{1}^{\prime }\left (t \right ) = x_{1} \left (t \right )-5 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = x_{1} \left (t \right )+3 x_{2} \left (t \right )] \]

633

\[ {}[x_{1}^{\prime }\left (t \right ) = 5 x_{1} \left (t \right )-9 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 2 x_{1} \left (t \right )-x_{2} \left (t \right )] \]

634

\[ {}[x_{1}^{\prime }\left (t \right ) = 3 x_{1} \left (t \right )-4 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 4 x_{1} \left (t \right )+3 x_{2} \left (t \right )] \]

635

\[ {}[x_{1}^{\prime }\left (t \right ) = 7 x_{1} \left (t \right )-5 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 4 x_{1} \left (t \right )+3 x_{2} \left (t \right )] \]

636

\[ {}[x_{1}^{\prime }\left (t \right ) = -50 x_{1} \left (t \right )+20 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 100 x_{1} \left (t \right )-60 x_{2} \left (t \right )] \]

637

\[ {}[x_{1}^{\prime }\left (t \right ) = 4 x_{1} \left (t \right )+x_{2} \left (t \right )+4 x_{3} \left (t \right ), x_{2}^{\prime }\left (t \right ) = x_{1} \left (t \right )+7 x_{2} \left (t \right )+x_{3} \left (t \right ), x_{3}^{\prime }\left (t \right ) = 4 x_{1} \left (t \right )+x_{2} \left (t \right )+4 x_{3} \left (t \right )] \]

638

\[ {}[x_{1}^{\prime }\left (t \right ) = x_{1} \left (t \right )+2 x_{2} \left (t \right )+2 x_{3} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 2 x_{1} \left (t \right )+7 x_{2} \left (t \right )+x_{3} \left (t \right ), x_{3}^{\prime }\left (t \right ) = 2 x_{1} \left (t \right )+x_{2} \left (t \right )+7 x_{3} \left (t \right )] \]

639

\[ {}[x_{1}^{\prime }\left (t \right ) = 4 x_{1} \left (t \right )+x_{2} \left (t \right )+x_{3} \left (t \right ), x_{2}^{\prime }\left (t \right ) = x_{1} \left (t \right )+4 x_{2} \left (t \right )+x_{3} \left (t \right ), x_{3}^{\prime }\left (t \right ) = x_{1} \left (t \right )+x_{2} \left (t \right )+4 x_{3} \left (t \right )] \]

640

\[ {}[x_{1}^{\prime }\left (t \right ) = 5 x_{1} \left (t \right )+x_{2} \left (t \right )+3 x_{3} \left (t \right ), x_{2}^{\prime }\left (t \right ) = x_{1} \left (t \right )+7 x_{2} \left (t \right )+x_{3} \left (t \right ), x_{3}^{\prime }\left (t \right ) = 3 x_{1} \left (t \right )+x_{2} \left (t \right )+5 x_{3} \left (t \right )] \]

641

\[ {}[x_{1}^{\prime }\left (t \right ) = 5 x_{1} \left (t \right )-6 x_{3} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 2 x_{1} \left (t \right )-x_{2} \left (t \right )-2 x_{3} \left (t \right ), x_{3}^{\prime }\left (t \right ) = 4 x_{1} \left (t \right )-2 x_{2} \left (t \right )-4 x_{3} \left (t \right )] \]

642

\[ {}[x_{1}^{\prime }\left (t \right ) = 3 x_{1} \left (t \right )+2 x_{2} \left (t \right )+2 x_{3} \left (t \right ), x_{2}^{\prime }\left (t \right ) = -5 x_{1} \left (t \right )-4 x_{2} \left (t \right )-2 x_{3} \left (t \right ), x_{3}^{\prime }\left (t \right ) = 5 x_{1} \left (t \right )+5 x_{2} \left (t \right )+3 x_{3} \left (t \right )] \]

643

\[ {}[x_{1}^{\prime }\left (t \right ) = 3 x_{1} \left (t \right )+x_{2} \left (t \right )+x_{3} \left (t \right ), x_{2}^{\prime }\left (t \right ) = -5 x_{1} \left (t \right )-3 x_{2} \left (t \right )-x_{3} \left (t \right ), x_{3}^{\prime }\left (t \right ) = 5 x_{1} \left (t \right )+5 x_{2} \left (t \right )+3 x_{3} \left (t \right )] \]

644

\[ {}[x_{1}^{\prime }\left (t \right ) = 2 x_{1} \left (t \right )+x_{2} \left (t \right )-x_{3} \left (t \right ), x_{2}^{\prime }\left (t \right ) = -4 x_{1} \left (t \right )-3 x_{2} \left (t \right )-x_{3} \left (t \right ), x_{3}^{\prime }\left (t \right ) = 4 x_{1} \left (t \right )+4 x_{2} \left (t \right )+2 x_{3} \left (t \right )] \]

645

\[ {}[x_{1}^{\prime }\left (t \right ) = 5 x_{1} \left (t \right )+5 x_{2} \left (t \right )+2 x_{3} \left (t \right ), x_{2}^{\prime }\left (t \right ) = -6 x_{1} \left (t \right )-6 x_{2} \left (t \right )-5 x_{3} \left (t \right ), x_{3}^{\prime }\left (t \right ) = 6 x_{1} \left (t \right )+6 x_{2} \left (t \right )+5 x_{3} \left (t \right )] \]

646

\[ {}[x_{1}^{\prime }\left (t \right ) = 3 x_{1} \left (t \right )+x_{3} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 9 x_{1} \left (t \right )-x_{2} \left (t \right )+2 x_{3} \left (t \right ), x_{3}^{\prime }\left (t \right ) = -9 x_{1} \left (t \right )+4 x_{2} \left (t \right )-x_{3} \left (t \right )] \]

647

\[ {}[x_{1}^{\prime }\left (t \right ) = x_{1} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 2 x_{1} \left (t \right )+2 x_{2} \left (t \right ), x_{3}^{\prime }\left (t \right ) = 3 x_{2} \left (t \right )+3 x_{3} \left (t \right ), x_{4}^{\prime }\left (t \right ) = 4 x_{3} \left (t \right )+4 x_{4} \left (t \right )] \]

648

\[ {}[x_{1}^{\prime }\left (t \right ) = -2 x_{1} \left (t \right )+9 x_{4} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 4 x_{1} \left (t \right )+2 x_{2} \left (t \right )-10 x_{4} \left (t \right ), x_{3}^{\prime }\left (t \right ) = -x_{3} \left (t \right )+8 x_{4} \left (t \right ), x_{4}^{\prime }\left (t \right ) = x_{4} \left (t \right )] \]

649

\[ {}[x_{1}^{\prime }\left (t \right ) = 2 x_{1} \left (t \right ), x_{2}^{\prime }\left (t \right ) = -21 x_{1} \left (t \right )-5 x_{2} \left (t \right )-27 x_{3} \left (t \right )-9 x_{4} \left (t \right ), x_{3}^{\prime }\left (t \right ) = 5 x_{3} \left (t \right ), x_{4}^{\prime }\left (t \right ) = -21 x_{3} \left (t \right )-2 x_{4} \left (t \right )] \]

650

\[ {}[x_{1}^{\prime }\left (t \right ) = 4 x_{1} \left (t \right )+x_{2} \left (t \right )+x_{3} \left (t \right )+7 x_{4} \left (t \right ), x_{2}^{\prime }\left (t \right ) = x_{1} \left (t \right )+4 x_{2} \left (t \right )+10 x_{3} \left (t \right )+x_{4} \left (t \right ), x_{3}^{\prime }\left (t \right ) = x_{1} \left (t \right )+10 x_{2} \left (t \right )+4 x_{3} \left (t \right )+x_{4} \left (t \right ), x_{4}^{\prime }\left (t \right ) = 7 x_{1} \left (t \right )+x_{2} \left (t \right )+x_{3} \left (t \right )+4 x_{4} \left (t \right )] \]

651

\[ {}y^{\prime } = 2 x +1 \]

652

\[ {}y^{\prime } = \left (x -2\right )^{2} \]

653

\[ {}y^{\prime } = \sqrt {x} \]

654

\[ {}y^{\prime } = \frac {1}{x^{2}} \]

655

\[ {}y^{\prime } = \frac {1}{\sqrt {x +2}} \]

656

\[ {}y^{\prime } = x \sqrt {x^{2}+9} \]

657

\[ {}y^{\prime } = \frac {10}{x^{2}+1} \]

658

\[ {}y^{\prime } = \cos \left (2 x \right ) \]

659

\[ {}y^{\prime } = \frac {1}{\sqrt {-x^{2}+1}} \]

660

\[ {}y^{\prime } = x \,{\mathrm e}^{-x} \]

661

\[ {}y^{\prime } = -\sin \left (x \right )-y \]

662

\[ {}y^{\prime } = x +y \]

663

\[ {}y^{\prime } = -\sin \left (x \right )+y \]

664

\[ {}y^{\prime } = x -y \]

665

\[ {}y^{\prime } = y-x +1 \]

666

\[ {}y^{\prime } = x -y+1 \]

667

\[ {}y^{\prime } = x^{2}-y \]

668

\[ {}y^{\prime } = -2+x^{2}-y \]

669

\[ {}y^{\prime } = 2 x^{2} y^{2} \]

670

\[ {}y^{\prime } = x \ln \left (y\right ) \]

671

\[ {}y^{\prime } = y^{{1}/{3}} \]

672

\[ {}y^{\prime } = y^{{1}/{3}} \]

673

\[ {}y y^{\prime } = x -1 \]

674

\[ {}y y^{\prime } = x -1 \]

675

\[ {}y^{\prime } = \ln \left (1+y^{2}\right ) \]

676

\[ {}y^{\prime } = x^{2}-y^{2} \]

677

\[ {}2 x y+y^{\prime } = 0 \]

678

\[ {}2 x y^{2}+y^{\prime } = 0 \]

679

\[ {}y^{\prime } = y \sin \left (x \right ) \]

680

\[ {}\left (1+x \right ) y^{\prime } = 4 y \]

681

\[ {}2 y^{\prime } \sqrt {x} = \sqrt {1-y^{2}} \]

682

\[ {}y^{\prime } = 3 \sqrt {x y} \]

683

\[ {}y^{\prime } = 4 \left (x y\right )^{{1}/{3}} \]

684

\[ {}y^{\prime } = 2 x \sec \left (y\right ) \]

685

\[ {}\left (-x^{2}+1\right ) y^{\prime } = 2 y \]

686

\[ {}\left (x^{2}+1\right ) y^{\prime } = \left (1+y\right )^{2} \]

687

\[ {}y^{\prime } = x y^{3} \]

688

\[ {}y y^{\prime } = x \left (1+y^{2}\right ) \]

689

\[ {}y^{\prime } = \frac {1+\sqrt {x}}{1+\sqrt {y}} \]

690

\[ {}y^{\prime } = \frac {\left (x -1\right ) y^{5}}{x^{2} \left (2 y^{3}-y\right )} \]

691

\[ {}\left (x^{2}+1\right ) \tan \left (y\right ) y^{\prime } = x \]

692

\[ {}y^{\prime } = 1+x +y+x y \]

693

\[ {}x^{2} y^{\prime } = 1-x^{2}+y^{2}-x^{2} y^{2} \]

694

\[ {}y^{\prime } = y \,{\mathrm e}^{x} \]

695

\[ {}y^{\prime } = 3 x^{2} \left (1+y^{2}\right ) \]

696

\[ {}2 y y^{\prime } = \frac {x}{\sqrt {x^{2}-16}} \]

697

\[ {}y^{\prime } = 4 x^{3} y-y \]

698

\[ {}1+y^{\prime } = 2 y \]

699

\[ {}\tan \left (x \right ) y^{\prime } = y \]

700

\[ {}x y^{\prime }-y = 2 x^{2} y \]